Формирование экологического сознания в профессиональном становлении будущих учителей-химиков - Сейфуллина, Б.С.; Кубашева, Р.Н.; Утепкалиева, Г.И. (My University, 2013)
The article describesthe problemsenvironmental educationin the WestKazakhstan State University. M. Utemisovin the regionthat hoststhe largestgas condensate field. The mainprofessional,social and personalcompetencies thatare developedin thestudents'learning process.